Comparison of efficacy and safety between unilateral biportal endoscopic transforaminal lumbar interbody fusion versus uniportal endoscopic transforaminal lumbar interbody fusion for the treatment of lumbar degenerative diseases: a systematic review and meta-analysis - Yi Ding; Hao Chen; Gang Wu; Tao Xie; Liulong Zhu; Xuepeng Wang (BMC Musculoskeletal Disorders)
Abstract Background This meta-analysis was performed to comprehensively evaluate the efficacy and safety of unilateral biportal endoscopic transforaminal lumbar interbody fusion (UBE-TLIF) versus uniportal endoscopic transforaminal lumbar interbody fusion (Endo-TLIF) for the treatment of lumbar degenerative diseases. Methods We electronically searched PubMed, Embase, Scopus, Web of Science, the Cochrane Library, the Wanfang Database, and China National Knowledge Infrastructure to identify controlled clinical studies on the efficacy and safety of UBE-TLIF and Endo-TLIF for lumbar degenerative diseases from database establishment to December 2023. Two researchers screened the literature, extracted data, and evaluated the risk of bias of the included studies. They also recorded the authors, sample size, operative time, intraoperative blood loss, hospital length of stay, complication rate, fusion rate, visual analogue scale scores, and Oswestry disability index in each study. The meta-analysis was performed using RevMan 5.4 software provided by the Cochrane Library. Results Five studies involving 314 patients met the inclusion criteria for this meta-analysis. The UBE-TLIF group comprised 154 patients, and the Endo-TLIF group comprised 160 patients. UBE-TLIF was superior to Endo-TLIF in terms of the operative time and fusion rate. There were no significant differences in the intraoperative blood loss, hospital length of stay, complication rate, visual analogue scale scores, or Oswestry disability index between the two groups. Conclusion Both UBE-TLIF and Endo-TLIF can achieve satisfactory clinical results with respect to improving low back and leg pain in patients with lumbar degenerative diseases. However, UBE-TLIF has the advantages of a shorter operative time and higher fusion rate. Trial registration This study was registered in the International Prospective Register of Systematic Reviews (PROSPERO) (ID: CRD42023495076).